ANALISIS PENGARUH KOMUNIKASI BISNIS DAN PROMOSI TERHADAP KINERJA PEMASARAN (Studi Kasus Sari Teknik Motor Yamaha di Koba) - Lovely Savira Hakim, Brenda; Shinta Lestari, Deara; Novika (STIE IBEK Pangkalpinang, 2022)
This research was entitled: “Analisis Pengaruh Komunikasi Bisnis dan Promosi Terhadap Kinerja Pemasaran (Studi Kasus Sari Teknik Motor Yamaha di Koba)”. The purpose of this study was to determine the effect of business communication and promotion on marketing performance either partially or simultaneously. This research was conducted from February 2022 to June 2022. This study aims to analyze the effect of business communication and promotion on marketing performance, using a descriptive method with a quantitative approach with a view to finding the relationship between the independent variables (Business Communication and Promotion) and the dependent variable (Marketing Performance) using statistical formulas. While the statistical formula used to test the hypothesis is Multiple Regression Analysis. The sample in this study amounted to 85 respondents. The results of the study prove that: Business Communication has no positive and significant effect on Marketing Performance (Sari Teknik Motor Yamaha). This is evidenced by the analysis of the tcount value of 0.372 and the ttable value of 1.663. So the value of tcount 0.372 < from ttable of 1.663, so it can be concluded that the Business Communication variable affects Marketing Performance. Promotion has a positive and significant effect on Marketing Performance (Sari Teknik Motor Yamaha). This is evidenced by the analysis of the tcount value of 17,382 and the ttable value of 1,663. So the value of tcount is 17,382 > from ttable of 1,663, so it can be concluded that the Promotion variable does not affect Marketing Performance. Business Communication and Promotion have a positive and significant effect simultaneously on Marketing Performance. This is evidenced by the analysis of the Fcount value of 151,272 and the Ftable value of 3.11. So the value of Fcount, so that it can be concluded that the variable of Business Communication and Promotion on Marketing Performance. Based on the results of the coefficient of determination seen from the adjusted R2 value of 0.782. This means that Marketing Performance is influenced by Business Communication and Promotion by 78.2%, while the remaining 21.8% is influenced by other variables not examined in this study.